Local and Systemic Pathogenesis and Consequences of Regimen-Induced Inflammatory Responses in Patients with Head and Neck Cancer Receiving Chemoradiation - Elvio G. Russi; Judith E. Raber-Durlacher; Stephen T. Sonis (Hindawi Limited, 2014)
Treatment-related toxicities are common among patients with head and neck cancer, leading to poor clinical outcomes, reduced quality of life, and increased use of healthcare resources. Over the last decade, much has been learned about the pathogenesis of cancer regimen-related toxicities. Historically, toxicities were separated into those associated with tissue injury and those with behavioural or systemic changes. However, it is now clear that tissue-specific damage such as mucositis, dermatitis, or fibrosis is no longer the sole consequence of direct clonogenic cell death, and a relationship between toxicities that results in their presentation as symptom clusters has been documented and attributed to a common underlying pathobiology. In addition, the finding that patients commonly develop toxicities representing tissue injury outside radiation fields and side effects such as fatigue or cognitive dysfunction suggests the generation of systemic as well as local mediators. As a consequence, it might be appropriate to consider toxicity syndromes, rather than the traditional approach, in which each side effect was considered as an autonomous entity. In this paper, we propose a biologically based explanation which forms the basis for the diverse constellation of toxicities seen in response to current regimens used to treat cancers of the head and neck.